Extensive rod and cone photoreceptor-cell degeneration in rat models of giant axonal neuropathy: implications for gene therapy of human disease. (3rd September 2021) - Armao, Diane; Bouldin, Thomas W.; Bailey, Rachel M.; Gray, Steven J.
ABSTRACT: Background : Giant axonal neuropathy (GAN; ORPHA: 643; OMIM# 256850) is a rare, hereditary, pediatric neurodegenerative disorder associated with intracellular accumulations of intermediate filaments (IFs). Validation of therapeutic efficacy and viral vector delivery systems with GAN knockout (KO) mouse models has provided the springboard for the development of a viral vector being delivered intrathecally in an ongoing Phase I gene therapy clinical trial for the treatment of children with GAN (https://clinicaltrials.gov/ct2/show/NCT02362438 ). Purpose : To characterize the ocular pathologic phenotype of newly developed GAN rat models. Materials and Methods : Microscopic examination of eyes at various timepoints. Results : We noted the unexpected finding of progressive and extensive degeneration of rod and cone photoreceptor (PR) cells in the retinas of GAN rat models. Conclusion : This PR-cell loss in rat models of GAN raises the possibility that PR-cell loss may contribute to the visual impairment observed in human GAN. The intrathecal viral vector employed in the ongoing Phase I gene therapy clinical trial for the treatment of children with GAN was not specifically designed to address PR-cell degeneration. If GAN-associated PR-cell loss is present and clinically significant in humans, then future treatment protocols for GAN may need to include a gene transfer approach or combinatorial treatment strategy that also targets retinal PR cells.